Robert Fox, Negritos and Philippine Prehistory - Kress, Jonathan H. (Hukay, 2016)
The ethnobotanical work of Robert B. Fox among the Negritos living in the vicinity of Mt. Pinatubo, Zambales Province, is taken as a starting point for an examination of the position of Negritos in Southeast Asian Prehistory. Early ethnographic and anthropometric investigations are reviewed along with more recent archaeological and genetic work. No study, ancient or contemporary, establishes an unquestionable unity between all the scattered Negrito populations of Asia and the Khoisan-pygmy populations of Africa on the one hand, and Australian-Papuan aboriginal populations on the other, although some evidence is tantalizingly suggestive of such a connection. The archaeological sequence of Palawan to which Fox made extensive contributions is examined.